(untitled) (Al-Academy, 2024)
This paper investigates the transformative function of Saudi songs in the analysis and influences of societal changes during the 1970s and 1980s. The research focuses on how music, including songs, helped and reflected quickly developing socio-cultural modifications associated with economic expansion and modernization in the country. The study is based on a qualitative strategy, counting on interviews conducted with cultural historians, and present music artists who can tell the tale of music’s consequences on culture. Eight participants were selected to participate in the research. The research evaluates how folk songs gathered and reflected Saudi society’s common thinking and changing values. The findings highlighted that Saudi songs could be viewed as artistic achievements, a mode of societal critique, and an instrument of cultural transformation. Moreover, the research findings include the remarkable changes in Saudi songs from the 1970s and 1980s and the increasing number of tracks devoted to certain moral and sociopolitical issues like social reforms, national pride, and changes in conventional values. Finally, the paper found that the Saudi songs from the 70s and 80s are pivotal in understanding the broader socio-political landscape of Saudi Arabia during these decades. Music significantly helped in the rapid alterations and formed the ways in which common Saudis recognized and lived through those adjustments Whether as a mode of societal engagement or an aspect of societal changes.